2017
DOI: 10.4103/jmas.jmas_109_16
|View full text |Cite
|
Sign up to set email alerts
|

Technique of totally robotic delta-shaped anastomosis in distal gastrectomy

Abstract: BACKGROUND:We aimed to clarify the utility of delta-shaped anastomosis (Delta), an intracorporeal Billroth-I anastomosis-based reconstruction technique used after laparoscopy-assisted distal gastrectomy (LADG), in robot-assisted distal gastrectomy (RADG).METHODS:RADG was performed in patients with clinical Stage I gastric cancer, and reconstruction was performed using Delta. The Delta procedure was the same as that performed after LADG, and the operator practiced the procedure in simulated settings with surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Narrow spaces surrounded by four surgical arms interfere with the assistants’ handling of the staplers. Kitagami et al 10 reported that the robotic arms interfere with the surgical field, hence the assistant use the stapler through the space between them in delta anastomosis for robot-assisted distal gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Narrow spaces surrounded by four surgical arms interfere with the assistants’ handling of the staplers. Kitagami et al 10 reported that the robotic arms interfere with the surgical field, hence the assistant use the stapler through the space between them in delta anastomosis for robot-assisted distal gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few hospitals in mainland China have applied da Vinci robotic-assisted surgical system in use. Moreover, current literatures regarding the role of surgical robot are merely limited to novel technique [1316] and case reports [17, 18]. The potential of da Vinci robotic-assisted surgical system in this field remains far from being fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies to date have described Billroth I reconstruction during TRDG [34121314]. Linear-shaped gastroduodenostomy (LSGD), which avoids duodenal rotation and overlapping reconstruction in the anterosuperior direction, has been reported to overcome the anatomical limitations of the delta-shaped method and facilitates digestive tract reconstruction [15].…”
Section: Introductionmentioning
confidence: 99%